Social, political and ecclesiastical criticism in the work of Ricardo Palma - Bunoro, Aura Cristina (2023)
The figure of Ricardo Palma has always aroused much interest both as creator of the masterpiece, Tradiciones peruanas which collects traditions, customs, pieces of history from every period of the country, the Inca Empire, the Colony, the Independence and the Republic, as well as the opponent of Manuel González Prada, in order to mention only a few perspectives. And on the basis of the last one, we come to the topic of the unfair annexation of the traditionist to colonialism and the discovery of the critical tone towards politics, Peruvian society and the church. These three great poles, considered as an extension of the colonial system, receive from Ricardo Palma a critical and ironic look and a comparison with what happened in the past in an attempt to offer Peruvians a better future without repeating mistakes. Keywords: criticism, society, politics, church, extension, colony.